(untitled) (Fountain Journal of Natural and Applied Sciences, 2013)
Dam water and sediment were collected from ten different locations on Owalla dam to evaluate the quality of the water. The average values of most physical-chemical parameters, the pH, temperature, total dissolved solid (TDS), NO3-, total hardness (TH) were within World Health Organization (WHO) and United State Environmental Protection Agency (USEPA) guidelines for drinking water. There was correlation between the results of Biochemical Oxygen Demand (BOD), sulphate and phosphate which were higher than the USEPA, Standard Organization of Nigeria (SON) or Canadian standard for drinking water. This is an indication of high load of organic pollutants. The dam sediments are texturally immatured coarse sands dominantly comprised of sub-angular to sub-rounded quartz, alkali feldspars with clay and iron-oxide coatings. The sediments geochemical composition is essentially silica, alumina and iron oxide. Toxic trace elements including Cd and Pb occur in very minor to insignificant concentrations with Igeo (index of geo-accumulation) values classifying the sediments as unpolluted. The sediments are also characterised by variably-high CIA (chemical index of alteration) values (av. 60) which is an indication that their derivation was from moderate to high tropical weathered source areas. Keywords: Owalla dam, physicochemical parameters, geo-accumulation index, chemical index of alteration, biochemical oxygen demand